а) (-5; 5) ⋂ (-3;2) = (-3; 2) - верно б) (4; 11) U (0; 6) =(0; 4) U (4; 6) U (6; 11) - неверно в) (-∞; 4) U (1; +∞) = (-∞; 1) U (1; 4) U (4; +∞) - неверно г) (-∞ 2) ⋂ (-2; +∞) = (-2; 2) - верно
2 votes Thanks 2
sedinalana
А (-5;5)∩(-3;2)=(-3;2) \\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\ ----(-5)--------(-3)--------(2)------(5)------- ///////////////// верно б (4;11)∪(0;6)=(0;11) ///////////////////////////////////////// -----(0)-------------(4)-----------(6)-------------(11)------- /////////////////////////////////////// неверно в (-∞;4) ∪(1;∞)=(-∞;1) U (1;4) U (4;∞) ///////////////////////////////////////// -----------(1)------------------(4)----------- /////////////////////////////////////////// неверно г (-∞;2)∩(-2;∞)=(-2;2) /////////////////////////////////////////////// ---------(-2)----------------------(2)--------------- \\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\ верно
Answers & Comments
Verified answer
U - объединение множеств⋂ - пересечение множеств
а) (-5; 5) ⋂ (-3;2) = (-3; 2) - верно
б) (4; 11) U (0; 6) =(0; 4) U (4; 6) U (6; 11) - неверно
в) (-∞; 4) U (1; +∞) = (-∞; 1) U (1; 4) U (4; +∞) - неверно
г) (-∞ 2) ⋂ (-2; +∞) = (-2; 2) - верно
(-5;5)∩(-3;2)=(-3;2)
\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\
----(-5)--------(-3)--------(2)------(5)-------
/////////////////
верно
б
(4;11)∪(0;6)=(0;11)
/////////////////////////////////////////
-----(0)-------------(4)-----------(6)-------------(11)-------
///////////////////////////////////////
неверно
в
(-∞;4) ∪(1;∞)=(-∞;1) U (1;4) U (4;∞)
/////////////////////////////////////////
-----------(1)------------------(4)-----------
///////////////////////////////////////////
неверно
г
(-∞;2)∩(-2;∞)=(-2;2)
///////////////////////////////////////////////
---------(-2)----------------------(2)---------------
\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\
верно